Implications of Islamic Values for Character Education of Students at SDIT Ahmad Yani Elementary School and SDN Landungsari 01 - Sindy Mulia Eka; Nurul Ulfatin; Asep Sunandar (Penerbit Hellow Pustaka, 2025)
This study explores the implementation of Islamic values in character education at SDIT Ahmad Yani and SDN Landungsari 01 using the inculcation approach. The aim of the research is to understand how Islamic values are integrated into educational activities and how this influences students' character development. The research employs a qualitative case study design, involving participatory observation, in-depth interviews, and document analysis. Findings reveal that at SDIT Ahmad Yani, programs such as congregational dhuha and zuhr prayers, group prayers, and Qur'an-related extracurricular activities strengthen students' moral and spiritual foundations. At SDN Landungsari 01, activities like congregational prayers and the Sitaya Bebudaya program at the mosque support moral development and national consciousness. Both schools effectively create students who are academically capable, ethically upright, and possess a strong national identity through the integration of Islamic values and the inculcation approach.